Pola Komunikasi Kiai dalam Membentuk Kemandirian Santri Berkebutuhan Khusus - Abdullah Jia (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Santri with special needs are students with symptoms of emotional barriers and display behaviour that is different from students in general, these disabilities can hinder their ability to communicate. Therefore, they must be handled in the right place, one of the suitable places to treat them is Padepokan Ibnu Rusydi Nglaban Diwek Jombang. The right kiai communication pattern has a positive impact on students with special needs, so they can live independently. This research aims to find out: 1) Kiai communication patterns in shaping the independence of special needs students at Padepokan Ibnu Rusydi; and 2) The form of independence of students with special needs in Padepokan Ibnu Rusydi. the results of this study indicate that: 1) The communication patterns applied by kiai are inter-personal communication, group communication, and instructional communication; and (2) forms of independence of special needs students include: independent self-care, independence in environmental hygiene and independence in carrying out worship activities